Characterisation, quantity and sorptive properties of microplastics extracted from cosmetics. Issue 1 (15th October 2015) - Napper, Imogen E.; Bakir, Adil; Rowland, Steven J.; Thompson, Richard C.
Highlights: Cosmetic products are potentially important sources of microplastics in the marine environment. Here we characterised and quantified plastic microbeads extracted from cosmetics. Extracted microbeads were polyethylene with mean diameters of between 164 and 327 μm. Between 4594 and 94, 500 microbeads could be released from an exfoliant in a single use. Extracted microbeads were able to sorb both Phe and DDT. Abstract: Cosmetic products, such as facial scrubs, have been identified as potentially important primary sources of microplastics to the marine environment. This study characterises, quantifies and then investigates the sorptive properties of plastic microbeads that are used as exfoliants in cosmetics. Polyethylene microbeads were extracted from several products, and shown to have a wide size range (mean diameters between 164 and 327 μm). We estimated that between 4594 and 94, 500 microbeads could be released in a single use. To examine the potential for microbeads to accumulate and transport chemicals they were exposed to a binary mixture of 3 H-phenanthrene and 14 C-DDT in seawater. The potential for transport of sorbed chemicals by microbeads was broadly similar to that of polythene (PE) particles used in previous sorption studies. In conclusion, cosmetic exfoliants are a potentially important, yet preventable source of microplastic contamination in the marine environment.